PROTEÇÃO ÀS VÍTIMAS DE CRIMES VIOLENTOS: REFLEXOS DE CASOS CONTENCIOSOS BRASILEIROS DA CORTE IDH - Vinicius Pedrosa Santos (2024)
This paper analyzes the protection of victims of violent criminal acts, especially in Brazilian court cases heard by the Inter-American Court of Human Rights (IACHR). First, a historical analysis of the evolution of the concept of violence and human rights was made, with an emphasis on the role of victims in this context. Understanding how the Inter American Court of Human Rights has defined and protected victims, examining the measures taken to safeguard them and evaluating the impact of decisions to which Brazil has been a party are the specific objectives of the research. The methodology employed is mainly qualitative, with bibliographical research, an analysis of documents and case law. The dissertation is divided into four chapters and discusses the different dimensions of violence, from its initial conceptions to contemporary approaches, including social, psychological, anthropological, political and cultural perspectives. It also addresses the reasons that lead to certain violent behaviors being criminalized, highlighting the importance of criminology and the role of victimology in this context. The study of victims is explored in detail in a specific chapter that considers their role throughout history, the levels of victimization and the development of human rights to protect them. This paper also analyzes victim protection mechanisms and how international law ensures these rights, with special attention to the UN's 2030 Agenda. The second chapter focuses on victim protection, examining its stage of global and national development, highlighting its handling in the United States and Brazil, as well as a detailed analysis of the Federal Assistance Program for Threatened Victims and Witnesses - PROVITA. The third chapter studies victim protection in the Inter-American Human Rights System, exploring other regional systems and detailing the procedures before the Inter-American Court of Human Rights, as well as the preliminary injunctions and measures on the case's merits adopted to safeguard victims and the monitoring of compliance with the determinations of the judgment on the case's merits. Finally, the fourth chapter analyzes the contentious cases in which Brazil was a party and was judged by the IA Court, evaluating the measures determined and the impact of these decisions on Brazilian domestic law, especially with regard to the protection of victims of violent crimes. The study seeks to identify changes in the future conduct of Federal authorities, public bodies, Legal practitioners and citizens in general, in accordance with the normative framework of human rights. The dissertation aims to contribute to improving the protection of victims of violent crimes in Brazil, to encourage greater compliance with the decisions of the Inter-American Court of Human Rights by legal professionals and to promote the respect and guarantee of fundamental human rights.